Pengaruh Konsentrasi Gliserol Terhadap Karakteristik Edible Film Pati Ubi Jalar (Ipomoea batatas L.) - Anjani Fatnasari; Komang Ayu Nocianitri; I Putu Suparthana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
Edible films is a thin layer packaged which produced from biopolymers and food-grade additives which is biodegradable in consumtion and environment. Sweet potato starch is one of many hydrocolloid which can be made as the material of edible film. Glycerol added in the formulation of edible film as a plasticizer to increase the characteristic of edible film. The purpose of this research is to determine glycerol concentration which it had best physic and chemist characteristics of edible film. The method of this research was completely randomized design with four grade of glycerol concentration there are 10%, 15%, 20% and 25% (v/b starch) which repeated four times. There are many parameters which analyzed in this research there are moisture content, thickness, water vapor transmission rate (WVTR), elongation and tensile strength. Data was analyzed with ANOVA and continued with Duncan’s (?=5%). The result of the research are increasing the glycerol concentration were influence amount of water moisture, thickness, elongation and tensile strength, but it is not influence the amount of water vapour transmission rate edible film. Best characteristic of edible film shown in formulation 10% (v/b starch) glycerol with amount of water moisture 12,50%, thickness 0,06 mm, WVTR 1,79 g/m2, elongation 8,75% and tensile strength 0,75 MPa.